Kontribusi Gaya Kepemimpinan, Kompetensi Pedagogik Danmotivasi Kerja Terhadap Kinerja Guru SMA Negeri Kota Surakarta - Suratno, Suratno; , Dr. Suyatmini, M.Si; , Drs. Syamsudin, M.M (2014)
The purpose of this study to determine and analyze 1) Contributions style of leadership on teacher performance SMA city of Surakarta, 2) Contributions pedagogical on teacher performance SMA city of Surakarta, 3) Contributions motivation to work has contributed significantly to the performance of State High School teacher Surakarta City, 4 ) Contributions style of leadership, pedagogical competence and motivation together have a significant contribution to the performance of State High School teacher of Surakarta. The population used in this study are all teachers SMA in Surakarta as much as 606 people. The sampling technique used in this research is proportional random sampling. The sample used in this study as many as 235 people. The research data was collected using a questionnaire (questionnaire). Data analysis techniques using multiple linear regression (Multiple Linear Regression). The conclusion of this study is the result of a count equal to 207.580 F or p-value <0.05 it can be concluded that jointly leadership style, pedagogical and motivational effect on performance. From the research that has been done shows that the test is no significant effect between kepeminpinan style, pedagogical competence and motivation on teacher performance. This suggests that in performing their duties very supportive leadership style advancement of teacher performance.